2020
DOI: 10.7759/cureus.10501
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Virucidal Effect of Intranasally Delivered Chlorpheniramine Maleate Compound Against Severe Acute Respiratory Syndrome Coronavirus 2

Abstract: Background The initial global outbreak of the novel coronavirus disease 2019 (COVID-2019) pandemic, which is responsible for the severe acute respiratory syndrome 2 (SARS-CoV-2), shares similarities with the severe acute respiratory syndrome coronavirus (SARS-CoV) and Middle East respiratory syndrome coronavirus (MERS-CoV) and behaves similarly to influenza with a high intranasal viral load. The genome sequence of COVID-19 opened the opportunity for multiple in vitro and clinical trials, but we stil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Second, most of the medications that treat respiratory diseases work in the organs of the respiratory system rather than in the periphery (Labiris and Dolovich 2003 ). The development of nasal spray treatments for SARS-CoV-2 is underway, and early clinical studies have confirmed that this approach is safe and can be used to prevent respiratory spread of SARS-CoV-2 (Westover et al 2020 ; Zhang et al 2020 ). Inhaled antibodies have the potential to be employed as a treatment, particularly for individuals who are not hospitalised and have a lower pathogen load.…”
Section: Inhaled Delivery In Special Context To Sars-cov-2 As a Future Prospectivementioning
confidence: 99%
“…Second, most of the medications that treat respiratory diseases work in the organs of the respiratory system rather than in the periphery (Labiris and Dolovich 2003 ). The development of nasal spray treatments for SARS-CoV-2 is underway, and early clinical studies have confirmed that this approach is safe and can be used to prevent respiratory spread of SARS-CoV-2 (Westover et al 2020 ; Zhang et al 2020 ). Inhaled antibodies have the potential to be employed as a treatment, particularly for individuals who are not hospitalised and have a lower pathogen load.…”
Section: Inhaled Delivery In Special Context To Sars-cov-2 As a Future Prospectivementioning
confidence: 99%
“…Many antihistamine drugs are also CAD and as such could act on virus entry while, also exerting a negative regulation on IL-6 release from human lung macrophages which are secreted in great amounts during the cytokine-storm of COVID-19 [ 10 , 11 ]. The most recent data indicate that antihistamines (anti-H 1 ) medications in general and particularly phenothiazines and derivates could be a useful strategy against SARS-CoV-2 at multiple stages, from prophylaxis to preventing complications of the infection itself [ [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] ]. Moreover, in a large sample of 219,000 electronic health records, 3 antihistamine medications (azelastine, diphenhydramine and hydroxyzine) were associated with reduced incidence of SARS-CoV-2 in subjects above the age of 61 [ 17 ],.…”
Section: Pharmacochemical Based Hypothesismentioning
confidence: 99%
“…A study conducted on SARS-cov-2 stock to highlight the virucidal potential of CPM showed a reduction of 99.7% in viral load in Vero 76 infected cells. [7] Mostafa et al in a study on FDA approved drugs that have potent antiviral activity against SARS-CoV-2 concluded that besides antimicrobial drugs like Azithromycin, Niclosamide, and Nitazoxanide, several antihistamines and anti-inflammatory drugs could reduce SARS-CoV-2 replication in vitro. Of these, Chlorpheniramine maleate, a competitive histamine H1 receptor antagonist, exhibited strong virucidal activity against a broad spectrum of influenza viruses.…”
Section: Discussionmentioning
confidence: 99%